Tasauf dan Kosmologi - Fuad Mahbub Siraj (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2014)
Mysticism or sufism is an activity that is focused on the esoteric aspect of Islam. It is totally different from the orientation of fiqh and sharī‘a which are more directed to the exoteric in Islam. Cosmology is the origin of the universe and the occurrence, and Ibn ‘Arabī is one of the sufi who discussed the issues of universe. In the works of Ibn ‘Arabī, the term of ‘ālam is translated by the Western researchers with cosmos. The cosmos or universe is defined as everything other than Allah (mā siwā Allah or al-Ḥaqq.) Ibn ‘Arabī’s cosmology essentially is called as prophetic cosmology (apostolic.) This knowledge is a form of knowledge that was transmitted from the Prophet Ādam to the Prophet Muḥammad, however, in grounding it, Ibn ‘Arabī limited it to the prophetic knowledge in the Qur’ān and Ḥadīth.